2020
DOI: 10.6065/apem.2040028.014
|View full text |Cite|
|
Sign up to set email alerts
|

Eating speed and the risk of type 2 diabetes: explorations based on real-world evidence

Abstract: Metabolic syndrome, especially diabetes, has gained global attention over the past few decades and became one of the major public health concerns. Alongside known and well-established risk factors, eating behaviors, mainly eating speed has shown the potential as one of the novel risk factors that could supplement the development of diabetes. However, there is a paucity in evidence, and only a few studies have addressed this question so far. In this review, with a focus on eating speed and the risk of developin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Several studies have investigated the impact of eating speed in this context and demonstrated its association with obesity and diabetes. [4][5][6][7][8][9][10][11][12][13] For instance, a Japanese study conducted on a large cohort of 197 825 participants over a period of 3 years reported that eating fast was the sole predisposing factor among several eating habits that led to new-onset diabetes. 5 Studies have found that obesity, 8 insulin resistance 14 15 and postprandial glucose metabolism, 16 which are all affected by eating speed, influence one another and cause diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have investigated the impact of eating speed in this context and demonstrated its association with obesity and diabetes. [4][5][6][7][8][9][10][11][12][13] For instance, a Japanese study conducted on a large cohort of 197 825 participants over a period of 3 years reported that eating fast was the sole predisposing factor among several eating habits that led to new-onset diabetes. 5 Studies have found that obesity, 8 insulin resistance 14 15 and postprandial glucose metabolism, 16 which are all affected by eating speed, influence one another and cause diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally advocated for nutritional intervention are education about portion control, improved product labeling, and the consumption of frequent meals to prevent snacking [36]. In addition, because eating fast and the risk of developing T2DM are highly associated, slow eating should be taught as an important eating habit [40]. According to a systematic review of 107 trials, low-carbohydrate diets had weight reduction outcomes proportional to those of low-fat diets and had no particularly negative impact on blood pressure, insulin, fasting serum glucose, or cholesterol levels [39].…”
Section: ) Lifestyle Modifications and Behavioral Treatmentmentioning
confidence: 99%
“…2) In addition to genetic and environmental factors, risk factors for T2D include advanced age, race/ethnicity, obesity, physical inactivity, high blood pressure, and sedentary lifestyle. [3][4][5] Thus, it is essential to identify modifiable risk factors causing T2D. Dairy products are important constituents of any diet, and the hormones present in dairy products, especially milk, are considered essential for growth and immunity.…”
Section: Introductionmentioning
confidence: 99%
“…T2D is a major public health concern, as 1 in 11 adults globally have T2D [ 2 ]. In addition to genetic and environmental factors, risk factors for T2D include advanced age, race/ethnicity, obesity, physical inactivity, high blood pressure, and sedentary lifestyle [ 3 - 5 ]. Thus, it is essential to identify modifiable risk factors causing T2D.…”
Section: Introductionmentioning
confidence: 99%